Dielectric properties of complex structured (1-x)Pb(Zr0.52Ti0.48)O3- X(Bi3.25La0.75)Ti3O12ceramics - Navavan Thongmee (2018)
The ceramics with formula (1-x)PZT - xBLT were fabricated by a solid-state reaction method. X-ray diffractometry indicated complete solid solutions occurred for all compositions. Perovskite phase with tetragonal crystal structure and corresponding lattice distortion was observed. PZT-rich ceramics also possessed relatively high densities due to their more equiaxed grains with high packing capability compared to the ceramics with an addition of plate-shaped BLT. Measurement of dielectric constant indicated a gradual decrease with increasing BLT content. PZT ceramic exhibited a peak of phase transition, while broader peak were seen for PZT - BLT solid solutions, suggesting more diffuse transformation occurred due to an addition of BLT. A shift of transition temperature (Tc) to lower temperature was also observed in the PZT - BLT solid solutions. Copyright © Taylor & Francis Group, LLC.